KOMUNIKASI BUDAYA DALAM PENDIDIKAN MEMBANGUN JEMBATAN PEMBELAJARAN ANTARBUDAYA - Putri Stevani A; Desy Misnawati (Bajang Institute, 2024)
Cultural communication is what occurs between people who have different cultures, be they racial, ethnic, or socio-economic, or a combination of all of these differences. Culture is a way of life that develops and is adopted by society and lasts from generation to generation. Cultural communication plays a role in education because it can broaden students' knowledge and learning experiences and open their knowledge horizons. Cultural communication also has an important role in terms of broadening understanding and improving intercultural relations and building strong bridges between students from different cultural backgrounds. Meanwhile, this communication can become a venue for cultural exchange in terms of education and also create effective communication strategies. effective in facilitating intercultural learning such as inclusive use of language, respect for differences, and promotion of cross-cultural cooperation in education